As espécies de tauari (Lecythidaceae) em florestas de terra firme da Amazônia: padrões de distribuição geográfica, abundâncias e implicações para a conservação - Procópio, Lilian Costa; Gayot, Marc; Plinio, Sist; Ferraz, Isolde Dorothea Kossmann (Acta Botanica Brasilica, 2010)
Understanding the range of a species is essential to understanding its ecology and conservation. In this study we collected data on the composition, abundance, diametric structure, and geographic distribution of "tauari" species (Lecythidaceae), which are among the most exploited timber trees of the Amazonian forest. We used herbarium data to define the areas of distribution and inventories of 401.25 ha from six areas of Amazonia to list species for estimating abundance and diametric structure. Of the 14 species that occur in the biome, nine were sampled in the inventories. Couratari guianensis had the largest continuous area of distribution, but always at low densities. Couratari stellata had the second largest distribution, but it was discontinuous and usually at high densities. Cariniana micrantha and Couratari multiflora had wide distributions and variable densities, whereas most of the other species showed regional or restricted ranges and densities below one individual per hectare. The classification of species according to rarity type diverged from that described for Couratari guianensis and C. multiflora. These results point out the lack of data for timber species in the most deforested regions of Amazonia, the need for local and regional abundance investigation for better understanding of distribution patterns, and to provide support for reviewing the categories and criteria of threats of Couratari species on the IUCN Red List.
Tauari species (Lecythidaceae) in non-flooded Amazon forest: patterns of geographic distribution, abundance, and implications for conservation
Keywords: Couratari; Diameter Structure; Rare Species; Forest Management; Timber Species; Couratari; Espécies Madeireiras; Espécies Raras; Estrutura Diamétrica; Manejo Florestal